Evaluation of proton pump inhibitor use on treatment outcomes with ledipasvir and sofosbuvir in a real‐world cohort study. Issue 6 (5th October 2016) - Tapper, Elliot B.; Bacon, Bruce R.; Curry, Michael P.; Dieterich, Douglas T.; Flamm, Steven L.; Guest, Lauren E.; Kowdley, Kris V.; Lee, Yoori; Tsai, Naoky C.; Younossi, Zobair M.; Afdhal, Nezam H.
Abstract : Many patients with chronic hepatitis C virus (HCV) are on prolonged proton‐pump inhibitor (PPI) therapy and wish to remain on PPI therapy once treatment for HCV starts. A preliminary report recently suggested decrease rates of sustained virological response (SVR) for patients taking concomitant PPI and ledipasvir/sofosbuvir (LDV/SOF). We sought to determine the effect of PPI use on the rate of SVR in a real‐world cohort of 1, 979 patients with chronic HCV treated with LDV/SOF. We collected clinical data and pharmacy dispensing records on patients taking 8, 12, or 24 weeks of LDV/SOF ± ribavirin (RBV). The primary outcome was sustained virological response at 12 weeks after treatment completion (SVR12) in a per‐protocol analysis in order to determine the effect of PPI use adjusted for confounders. Statistical adjustment was performed in propensity‐matched analysis. Among treatment completers, SVR12 was achieved in 441 (97.1%) of PPI recipients compared with 1, 497 (98.2%) in PPI nonrecipients ( P = 0.19). Neither low‐ nor high‐dose PPI was associated with decreased SVR, although patients taking twice‐daily PPI achieved a lower SVR12 rate (91.2%; 95% confidence interval [CI], 77.0‐97.0; P = 0.046). After propensity matching for PPI use, there were no significant associations between SVR12 and any dose or frequency of PPI use. However, in a sensitivity analysis focusing on patients with cirrhosis, twice‐daily PPI use was associated with lower odds ratio for SVR12 (0.11; 95% CI, 0.02‐0.59). Conclusion: These data from a cohort of real‐world patients receiving hepatitis C antibody therapy with LDF/SOF ± RBV support the prescription labeling suggesting that patients take no more than low‐dose (20‐mg omeprazole equivalents) PPI daily. (Hepatology 2016;64:1893‐1899).